Introduction to modern biophysics - Ashrafuzzaman, Mohammad (Boca Raton : CRC Press, 2024)
This textbook provides an introduction to the fundamental and applied aspects of biophysics for advanced undergraduate and graduate students of physics, chemistry, and biology. The application of physics principles and techniques in exploring biological systems has long been a tradition in scientific research. Biological systems hold naturally inbuilt physical principles and processes which are popularly explored. Systematic discoveries help us understand the structures and functions of individual biomolecules, biomolecular systems, cells, organelles, tissues, and even the physiological systems of animals and plants. Utilizing a physics- based scientific understanding of biological systems to explore disease is at the forefront of applied scientific research.
Keywords: Biophysics; Biomolecules; Surface biophysics